The Implementation of Government Public Relations (GPR) in Anticipating the Issue of Covid-19 Case Surge Through Social Media (Content Analysis of Instagram @lawancovid19_id During the Early Phase of Omicron) - Ramadhani, Amirah Azzahra; Nasrullah, Nasrullah; Erliani, Sri (Riwayat: Educational Journal of History and Humanities, 2025)
This study discusses the implementation of Government Public Relations (GPR) in anticipating the spike in COVID-19 cases during the early phase of the Omicron variant through social media, with a case study of Instagram content analysis @lawancovid19_id. The results of the study indicate that the implementation of GPR by the government has not fully met the eight objectives of GPR, according to Mordecai Lee, but only covers three main aspects, namely providing public information, reporting to the public, and educating the public. The government has shown an improvement in communication strategy compared to the previous pandemic phase with information transparency regarding policies and preventive measures taken. However, the use of social media is still limited to one-way communication in the form of disseminating information without significant interaction with the public. The stage of information socialization still dominates the implementation of government social media (GSM), and it has not moved on to the stage of collaboration or social transactions. In addition, the role of public relations organizations such as Public Relations Association and Bako-Humas is still not seen significantly in managing crisis communications nationally. The results of this study indicate that the effectiveness of GPR and GSM in dealing with the spike in COVID-19 cases can still be improved, especially in terms of public interaction and involvement through social media.